Chronic glucokinase activator treatment at clinically translatable exposures gives durable glucose lowering in two animal models of type 2 diabetes. (April 2014) - Baker, D J; Wilkinson, G P; Atkinson, A M; Jones, H B; Coghlan, M; Charles, A D; Leighton, B
<x xml:space="preserve">Abstract</x> Background and Purpose Pharmacological activation of glucokinase (GK) lowers blood glucose in animal models and humans, confirming proof of concept for this mechanism. However, recent clinical evidence from chronic studies suggests that the glucose‐lowering effects mediated by glucokinase activators (GKAs) are not maintained in patients with type 2 diabetes (T2D). Existing preclinical data with GKAs do not explain this loss of sustained glucose‐lowering efficacy in patients. Here, we have assessed the effects of chronic (up to 11 months) treatment with two different GKAs in two models of T2D. Experimental Approach Two validated animal models of T2D, insulin‐resistant obese Zucker rats and hyperglycaemic gkwt/del mice, were treated with two different GKAs for 1 or 11 months respectively at exposures that translate to clinical exposures in humans. Blood glucose, cholesterol, triglycerides and insulin were measured. GKA pharmacokinetics were also determined. Key Results Treatment with either GKA provided sustained lowering of blood glucose for up to 1 month in the Zucker rat and up to 11 months in hyperglycaemic gkwt/del mice, with maintained compound exposures. This efficacy was achieved without increases in plasma or hepatic triglycerides, accumulation of hepatic glycogen or impairment of glucose‐stimulated insulin secretion. Conclusions and Implications Chronic treatment with two GKAs in two animal models of diabetes provided sustained lowering of blood glucose, in marked contrast to clinical findings. Therefore, either these animal models of T2D are not good predictors of responses in human T2D or we need a better understanding of the consequences of GK activation in humans.